Method for improving light efficiency of fluorescent powder
Patent Information
- Application Number
- CN202410100133.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-24
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-01-24
AI Technical Summary
氮化物荧光粉的激发光谱一般在350nm-620nm之间,铝酸盐荧光粉的发射光谱为500nm-590nm,所以铝酸盐发出的光同样可以被上层的氮化物吸收转化,造成二次吸收转化,从而降低转化效率
1、本发明涉及荧光粉生产过程中的一种新的工艺,具体的说是一种可以在现有的荧光粉颗粒的基础上来完善荧光粉颗粒粒径和形貌,使相同材质和不同材质的荧光粉、相同粒径不同形貌荧光粉生产为粒径相同、形貌相同且密度相当的荧光粉。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of phosphor production, specifically a new process for improving the particle size and morphology of phosphor particles and enhancing the luminous efficacy of phosphors based on existing phosphor particles. Background Technology
[0002] Currently, there are many types of phosphors, and the density and morphology of phosphors of different materials vary greatly. For example, commonly used aluminate phosphors have a spherical morphology, nitride phosphors have a cuboid morphology, and silicate phosphors have an irregular morphology. Furthermore, the density of phosphors of different materials varies considerably. In LED packaging, commonly used phosphors are mainly divided into aluminate phosphors and nitride phosphors. Aluminate phosphors are further divided into gallium aluminate and lutetium aluminate phosphors. Gallium aluminate phosphors generally have a density of 4.9 g / cm³ and a regular spherical shape; lutetium aluminate phosphors generally have a density of 6.7 g / cm³ and a regular spherical shape; nitride phosphors generally have a density of 3.6 g / cm³ and are usually elongated or flat. In the LED lamp production process, to achieve different color temperatures, color rendering indices, and brightness levels, phosphors of different particle sizes, materials, and wavelengths need to be mixed and encapsulated. During the encapsulation process, phosphors of different materials and particle sizes settle at different rates in the encapsulation adhesive, resulting in unstable encapsulation processes. Consequently, the finished LED beads exhibit significant deviations in color temperature, color rendering index, and CIE landing point, leading to low production yield and high costs.
[0003] Furthermore, LED packaging typically employs a combination of blue LED chips, aluminate phosphors, and nitride phosphors to meet the requirements for white light and color rendering index. Due to differences in morphology and density, aluminate phosphors descend faster in the encapsulating adhesive and remain at the bottom layer, while nitride phosphors descend slower and remain on top. The excitation spectrum of nitride phosphors is generally between 350nm and 620nm, while the emission spectrum of aluminate phosphors is between 500nm and 590nm. Therefore, the light emitted by aluminate phosphors can also be absorbed and converted by the upper nitride layer, resulting in secondary absorption and conversion, thus reducing conversion efficiency.
[0004] In summary, when phosphors of different particle sizes, materials, and wavelengths are mixed and used in the LED packaging process, there are problems such as large deviations in the color temperature, color rendering index, and CIE landing point of the finished LED beads, as well as low conversion efficiency and low production yield. Summary of the Invention
[0005] The purpose of this invention is to provide a method for improving the luminous efficacy of phosphors. This method can increase the phosphor particle size and make the phosphor particle size more uniform, thereby ensuring the consistency of LED chip packaging process. At the same time, it can improve the aging resistance and reliability of phosphors, and improve the production yield and luminous efficacy of LED chips.
[0006] This invention is implemented as follows: The method for improving the luminous efficacy of phosphors provided by this invention first involves coating the surface of phosphors with adhesive using a spray granulation method, followed by encapsulation of the coated phosphors. Specifically, this invention utilizes a spray granulation method, first adding phosphors to the encapsulation adhesive and stirring it evenly. Then, adjusting the spray volume of the nozzle controls the particle size of the coated phosphors. Next, adjusting the temperature and spray stroke of the spray granulator ensures the coated phosphors are thoroughly dried. Finally, the spray-granulated phosphors are sieved to remove particles whose particle size is outside the specified range, ultimately ensuring the uniformity of the particle size after coating.
[0007] The spray granulation process in this invention is carried out after the phosphor sintering and particle size classification are completed.
[0008] Phosphor usually refers to LED phosphor, and adhesive refers to LED encapsulation adhesive.
[0009] Furthermore, the method for improving the luminous efficacy of phosphors provided by the present invention includes the following steps: S1. Mix LED phosphor and LED encapsulating adhesive, with a mass ratio of LED phosphor to LED encapsulating adhesive of 1:0.5~3; S2. Thoroughly stir the mixed LED phosphor and LED encapsulation adhesive to ensure that the LED phosphor is evenly distributed in the LED encapsulation adhesive. S3. The well-stirred mixture is put into a spray granulator for spray granulation. By controlling the wind speed, spray volume, stroke and drying temperature, the particle size D50 of the spray granulated particles is controlled between 4 micrometers and 300 micrometers. S4. After drying, the particles are classified by particle size classification, with each 5-micron D50 stage being a classification stage.
[0010] Furthermore, the LED phosphor in step S1 is a commonly used aluminate, silicate, and / or nitride phosphor, with a particle size D50 between 5 and 25 micrometers. The emission spectrum peak of aluminate phosphor is generally between 500 nm and 590 nm, and it is basically a yellow-green phosphor, while the emission spectrum of nitride phosphor is generally between 600 nm and 700 nm, and it is a red phosphor.
[0011] Furthermore, in step S1, the LED phosphor can be a single-material phosphor or a mixed phosphor composed of several different materials to meet encapsulation requirements. For mixed phosphors of different materials, the mixed phosphor and LED encapsulation adhesive are mixed and thoroughly stirred to ensure that the mixed phosphor is evenly distributed in the adhesive, guaranteeing uniform phosphor distribution in each particle after spray granulation.
[0012] Furthermore, the LED encapsulation adhesive in step S1 refers to the encapsulation adhesive commonly used in LED chip encapsulation, including but not limited to resin adhesive, transparent silicone, and other adhesives that can be used for LED chip encapsulation.
[0013] Furthermore, the particle size classification method in step S4 can be a moisture method, an air classifier, or a physical sieving method, etc. For the physical sieving method, the uniformity of the particles is ensured by passing the phosphor particles through the sieve once or multiple times and stopping the sieve once or multiple times.
[0014] Furthermore, in step S3, during the spray granulation process, the drying temperature and stroke of the spray granulator are determined according to the curing temperature of different adhesives to ensure thorough drying. The resulting spray-granulated particles have a spherical morphology. Preferably, the particle size D50 of the finished spray-granulated particles is controlled at approximately 50 micrometers.
[0015] The present invention has the following beneficial effects: 1. This invention relates to a new process in the production of phosphors, specifically a process that can improve the particle size and morphology of phosphor particles based on existing phosphor particles, so that phosphors of the same material and different materials, and phosphors of the same particle size but different morphologies, can be produced into phosphors with the same particle size, the same morphology and the same density.
[0016] 2. This invention utilizes a spray granulation method to uniformly coat the surface of ordinary LED phosphors with a layer of LED encapsulation adhesive, thereby increasing the phosphor particle size. During the LED encapsulation process, when two or more phosphors of different materials and particle sizes are mixed, spray granulation ensures more uniform mixing and consistent settling speed. The two or more phosphor particles are evenly distributed in the adhesive, reducing the problem of secondary absorption between phosphors and improving the yield of CIE landing points in the encapsulation process.
[0017] 3. The present invention also includes mixing phosphors of different wavelengths together as required, and then spray granulating them. This ensures that the phosphors in each granulated particle are evenly distributed. Then, the particles are encapsulated to ensure the yield of the encapsulated LED beads.
[0018] 4. This invention utilizes a spray granulation method to coat the surface of phosphor with a layer of LED encapsulation adhesive, thereby increasing the phosphor particle size and making the phosphor particles more uniform and smooth. This also makes the density of phosphors of different materials closer, resulting in a more consistent settling rate of phosphors of different materials and particle sizes in the subsequent encapsulation process. This makes the encapsulation process more stable and improves the aging resistance and reliability of the phosphor.
[0019] 5. The method employed in this invention primarily addresses the secondary absorption problem of phosphors at two different wavelengths, thereby improving photoelectric conversion efficiency and enhancing the luminous efficacy and brightness of the packaged LED beads. Simultaneously, it resolves the CIE dropout yield issue arising from varying phosphor particle sizes during the packaging process, significantly improving production yield and substantially reducing production costs for packaging companies.
[0020] 6. The phosphors processed by the method of the present invention have basically the same particle morphology and density, and the settling velocity is also basically the same, which can greatly improve the stability of the encapsulation process.
[0021] 7. The phosphors treated by the method of the present invention have similar density and morphology, and similar settling speed. This reduces the absorption of light emitted by aluminate phosphors by nitride phosphors and reduces secondary absorption and conversion, thereby improving the luminous efficacy of LED beads.
[0022] 8. The phosphor improved by the method of the present invention can not only achieve high concentration of phosphor droplets after encapsulation, but also increase conversion efficiency and improve brightness. Attached Figure Description
[0023] Figure 1 These are comparative images of the BINs of the packaged products from the comparative examples 1-4. Detailed Implementation
[0024] The present invention will be further described below with reference to comparative examples and embodiments. The following embodiments are for illustrative purposes only and do not limit the scope of protection of the present invention in any way.
[0025] Comparative Example LED packaging is performed using existing technologies and processes: A commonly used encapsulation scheme with a color rendering index of 90 was selected. Phosphor A is an aluminate phosphor with a peak wavelength of around 530 nm, and phosphor B is a nitride phosphor with a peak wavelength of around 645 nm. Phosphor A and phosphor B are encapsulated. The parameters of phosphor A and phosphor B are shown in Table 1.
[0026] Table 1 Original parameters of phosphors A and B Following commonly used encapsulation methods, a conventional encapsulation scaffold was selected to encapsulate phosphor A and phosphor B according to the proportions in Table 2, and the results were tested. This experiment is defined as the comparative example.
[0027] Table 2. Standard Phosphor Ratio According to the standard phosphor ratio in Table 2, the glue, phosphor A, and phosphor B are thoroughly mixed. Vacuum degassing technology is used to remove air bubbles from the glue. Then, the glue is applied and encapsulated into LED beads. After encapsulation, the LED beads are tested, and the obtained photoelectric parameters are shown in Table 3 below.
[0028] Table 3. Photoelectric parameters after comparative packaging Unlike the comparative examples, in Embodiments 1-4 of the present invention, the phosphor is spray-granulated before LED encapsulation. The phosphor can be spray-granulated alone or mixed before spray-granulation. Encapsulation is then performed after spray-granulation.
[0029] Spray granulation can alter the particle size of phosphors. In this embodiment of the invention, phosphor A, phosphor B, and a mixture of phosphor A and phosphor B are respectively subjected to spray granulation. A detailed description follows.
[0030] Spray granulation of phosphor A 500g of phosphor A was thoroughly mixed with encapsulating adhesive and placed into a spray granulator. The parameters of the spray granulator were adjusted, namely the spray volume, wind speed, stroke and temperature, so that the particle size of the powder after spray granulation was 30μm, 50μm and 100μm. After sieving, phosphor C with D50 of 30μm, phosphor D with D50 of 50μm and phosphor E with D50 of 100μm were obtained respectively. The parameters of the obtained phosphors are shown in Table 4 below.
[0031] Table 4 Comparison of parameters before and after spray granulation of phosphor A Spray granulation of phosphor B 500g of phosphor B was thoroughly mixed with the encapsulating adhesive and placed into a spray granulator. The parameters of the spray granulator were adjusted so that the particle sizes of the powder particles after spray granulation were 30μm, 50μm, and 100μm. After sieving, phosphor F with a D50 of 30μm, phosphor G with a D50 of 50μm, and phosphor H with a D50 of 100μm were obtained respectively. The parameters of the obtained phosphors are shown in Table 5 below.
[0032] Table 5 Comparison of parameters before and after spray granulation of phosphor B Spray granulation of a mixture of phosphor A and phosphor B 470g of phosphor A and 46g of phosphor B were thoroughly mixed and then thoroughly mixed with the encapsulating adhesive. The mixture was then placed in a spray granulator. Since the phosphors had already been mixed, the particle size was set to 50μm for this spray granulation. The parameters of the spray granulator were adjusted so that the particle size of the powder after spray granulation was 50μm, resulting in phosphor I with a D50 of 50μm. The parameters of the obtained phosphor are shown in Table 6.
[0033] Table 6. Particle size parameters of mixed phosphors A and B after spray granulation Following the principle of using phosphors of the same particle size in combination, the phosphors after spray granulation were mixed and encapsulated or encapsulated separately, as shown in Examples 1-4 below. In each example, during the LED encapsulation process, after the adhesive and phosphor were thoroughly stirred evenly, vacuum degassing technology was used to remove air bubbles from the adhesive, followed by dispensing and encapsulation into LED beads, and photoelectric parameter detection was performed. Examples 1-4 are as follows.
[0034] Example 1 Phosphor C with a D50 of 30 μm after spray granulation was encapsulated with phosphor F. The phosphor formulation is shown in Table 7 below.
[0035] Table 7 Phosphor Ratio for Example 1 Example 2 Phosphor D with a D50 of 50 μm after spray granulation was encapsulated with phosphor G. The phosphor formulation is shown in Table 8 below.
[0036] Table 8. Phosphor ratio for Example 2 Example 3 Phosphor E with a D50 of 100 μm after spray granulation was encapsulated with phosphor H. The phosphor formulation is shown in Table 9 below.
[0037] Table 9. Phosphor ratio for Example 3 Example 4 Phosphor I with a D50 of 50 μm was obtained by spray granulation after mixing phosphor A and phosphor B. The phosphor formulation is shown in Table 10 below.
[0038] Table 10 Phosphor Ratio for Example 4 Photoelectric testing was performed on the products packaged in Examples 1 to 4. Twenty sets of tests were conducted for each example, and the resulting photoelectric parameters are shown in Tables 11 to 14.
[0039] Table 11 Photoelectric parameters after encapsulation in Example 1 Table 12 Photoelectric parameters after packaging in Example 2 Table 13 Photoelectric parameters after packaging in Example 3 Table 14 Photoelectric parameters after encapsulation in Example 4 The photoelectric parameters of the packaged products of Examples 1-4 were compared with those of the packaged products of the comparative example. The results are shown in Table 15.
[0040] Table 15 Comparison of photoelectric parameters after packaging in comparative examples and Examples 1-4 By comparing the encapsulation results of the comparative examples, Example 1, and Example 2, it can be concluded that after spray granulation, the phosphor particle size gradually increases, resulting in higher luminous efficacy after encapsulation (see Table 15) and better BIN drop yield (see Table 15). Figure 1 Comparing the encapsulation results of Examples 2 and 3, it can be concluded that increasing the coating particle size after the central particle size D50 is greater than 50μm does not significantly improve the luminous efficacy and BIN yield. Therefore, it can be concluded that for this phosphor solution, increasing the central particle size D50 of the phosphor to approximately 50μm via spray granulation yields the best results. Furthermore, comparing the comparative example and Example 4, it can be seen that increasing the phosphor particle size after spray granulation results in higher luminous efficacy after encapsulation. The comparison between Examples 2 and 4 shows that spray granulation of the phosphor separately before encapsulation and spray granulation of a mixture of phosphors before encapsulation produce products with similar luminous efficacy, both higher than the product in the comparative example.
Claims
1. A method for improving the luminous efficacy of phosphors, characterized in that, First, the phosphor is coated with adhesive using a spray granulation method, and then the phosphor coated with adhesive is encapsulated. The adhesive is coated onto the surface of the phosphor using a spray granulation method. The specific steps are as follows: (1) Mix the fluorescent powder and glue thoroughly, and then put them into a spray granulator; (2) Adjust the parameters of the spray granulator so that the particle size of the powder after spray granulation meets the set requirements; In step (1), the phosphor is a single phosphor or a mixture of multiple phosphors; The phosphor is LED phosphor, and the adhesive is LED encapsulation adhesive.
2. The method for improving the luminous efficacy of phosphor according to claim 1, characterized in that, The phosphor is an aluminate phosphor, silicate phosphor, and / or nitride phosphor, and the phosphor particle size D50 is between 5 and 25 μm.
3. The method for improving the luminous efficacy of phosphor according to claim 1, characterized in that, After spray granulation, the particle size D50 of the powder is controlled between 4 micrometers and 300 micrometers.
4. The method for improving the luminous efficacy of phosphor according to claim 1, characterized in that, In step (1), the mass ratio of fluorescent powder to adhesive is 1:0.5~3.
5. The method for improving the luminous efficacy of phosphor according to claim 1, characterized in that, In step (2), the parameters of the spray granulator are adjusted, specifically: the wind speed, spray volume, stroke and drying temperature of the spray granulator are adjusted.
6. The method for improving the luminous efficacy of phosphor according to claim 1, characterized in that, After spray granulation, the particles are classified by particle size classification, with each 5μm step representing a D50 stage.
7. The method for improving the luminous efficacy of phosphor according to claim 6, characterized in that, Particle size classification methods include moisture method, air classifier, or physical sieving method.
Citation Information
Patent Citations
Preparation method of high-efficiency spherical green fluorescent powder for white light LEDs (light-emitting diodes)
CN104371723A
Large-particle yttrium aluminum garnet(YAG) phosphor powder and composite auxiliary agent and method for preparing uniform large-particle YAG phosphor powder
CN106905970A